SPECIFIC FEATURES AND TOOLS OF BANK PROJECT FINANCING IN RUSSIA - Elina I. Abdyukova; Anna A. Sysoeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article investigates project financing as a specific type of bank financing. The authors analyze distribution of global volumes of project financing by sectors of economy and in the regional view. They also show the differences between project financing and other types of bank financing and classify key mechanisms of risk management in project financing. The authors came to the conclusion that further development of project financing in Russia is hindered by factors stipulated by specific features of banking and by certain macro-economic factors. Special attention is paid to methodology of selecting investment projects for crediting in the commercial bank and their monitoring as a tool which could reduce the negative effect of credit risks.